2022
DOI: 10.1155/2022/7500056
|View full text |Cite|
|
Sign up to set email alerts
|

Traditional Chinese Medicine Based Acupoint Application for Asthma Treatment in Children: A Meta-Analysis and Systematic Review

Abstract: Objective. By conducting a systematic review of the efficacy of acupoint application on children with asthma. Methods. We searched Chinese databases (CNKI, VIP, and Wanfang) and English databases (PubMed, Embase, and Cochrane Library) for studies from the establishment of the database to October 2021. The included literature studies were randomized control studies investigating the treatment of asthma in children by acupoint application. The primary outcomes included the cure rate, the resolution time of cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%